Teaching sustainable development goals and social development: a Case study teaching method. Issue 7 (3rd October 2022) - Addo, Reuben; Koers, Gregory; Timpson, William M.
ABSTRACT: The social development perspective and Sustainable Development Goals (SDGs) are central to international social work practice. SDGs and the social development perspective represent an intersection of multiple disciplinary paradigms. Thus, teaching SDGs and social development requires socialwork educators to use pedagogical approaches that provide a comprehensive understanding of real-life scenarios. Using case studies as a method of teaching has shown to improve student learning outcomes in sustainability education. Case studies offer students real-life scenarios to analyze and evaluate complex issues, and it equips students with the opportunity to explore and synthesize contextual factors and the interrelationships between SDGs. This article presents various case study formats in the classroom including written narratives, films, and guest speakers. We will discuss different types of case-study teaching strategies that can be used to improve learning outcomes in teaching SDGs and social development. This will include sustainability puzzles, iceberg, illustrative, and dialogue cases. The authors contextualize Case study teaching within a constructivist pedagogy that promotes critical thinking, collaboration, and problem-solving. Finally, we will discuss the potential implications of teaching SDGs and social development using case-studies on social work education.